Stereoselective Synthesis of Polyfunctionalized Nitrones through Conjugate Addition of α-Halo Hydrazones to Nitroso Compounds - Bi, Xiao-Fan; Pang, Hai-Liang; Tang, Zhe; Zhang, Heng; Cai, Lu-Yu; Wu, Hui-Hui; Fan, Xiao-Zu; Zhao, Hong-Wu (Synlett, 2021)
In the presence of Na2CO3, conjugate addition of α-halo hydrazones to nitroso compounds proceeded readily to give polyfunctionalized nitrones in reasonable chemical yields and excellent stereoselectivities. The chemical structure and the stereochemical configuration of the products were unambiguously identified by an X-ray single-crystal structural analysis.
Keywords: conjugate addition; halo hydrazones; nitroso compounds; nitrones; stereoselectivity